Assessment of sociable spaces in the central areas of jaffna town – an urban spatial planning perspective - Kajentiny, K. (University of Jaffna, 2018)
- Jaffna town is urbanizing rapidly as response to the growing economy of the region. Space demand for social interaction also increases in par with the demand for other uses. Urban Sociable spaces that refer to the publicly owned and managed outdoor spaces such as streets, parks, green open spaces, playgrounds, water bodies, facilitate social interaction and characterize the image and identify of a city. Jaffna town is unable to cater the needs in terms of sociable urban spaces, though there are different types of spaces available. This research aims to improve the quality of those spaces in order to cater the needs of urban communities. This research has been undertaken based on field survey of those spaces, observation of people who use those spaces, interview of potential beneficiaries, and planning professionals who design those spaces. Questionnaire survey of commuters and inhabitants was conducted to assess the needs to be enhanced in those spaces. The study shows that the people lack the habit of spending their time in sociable spaces though there are needs in the subconscious mind for recreational needs. The available spaces also polluted due to waste water discharge and solid waste disposal and not having necessary infrastructure facilities to attracting people and provide them safer and comfortable space. There are no clear land use zoning regulations to prohibit unauthorized developments and encroachments. Planning authorities also are not having ideas to incorporate the sociable aspect of development in the town areas. There are challenges to create sociable space within the town Centre since the level of saturated built environment. A strategic urban regeneration plan must incorporate provisions for improvement of environment, facilities and amenities of Fort promenade, Pullukulam, AriyaKulam, VannaanKulam and Subramaniumpark. Extensive awareness among the professionals and officers of planning and development also important to trigger the ideas from the grass root level.
Keywords: Green parks; Urban sociable space; Vibrantpublic space